Fisheries Commodity Trading Policy As Agribusiness In South Sulawesi - Hasanuddin Remmang; Hadijah Mahyuddin; Sitti Mujahida Baharuddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
This study aims to obtain the results of studies regarding the behavior of fishery commodity agribusiness development in the province of South Sulawesi. The analysis model in this study uses a structural equation model to examine the relationship between variables according to the proposed hypothesis. The variables studied in this study consist of exogenous variables, including production, marketing, and financial management capabilities. The intermediate variable in this study is the development of sales, and the variable increase in business profit is an endogenous variable. The three types of variables are built based on a theoretical approach that forms a constellation of relationships between variables, where each variable has dimensions and indicators. As for the respondents in this study, there were 250 fishing communities and people's aquaculture groups in Pangkep district. The results of the study found that generally, respondents from fishing communities and farmers had production, marketing, and financial management capabilities for increasing sales volume and increasing profits. Based on the results of this study, it is expected that the agribusiness of fishery commodities (sea and land fish) can develop through the role of the government and related parties so as to be able to improve people's living standards and increase regional income sources.